ULTRASAFE: ULTRASOUND LITERACY AND RADIOLOGY AWARENESS FOR SAFE EXAMINATIONS: ULTRASAFE: LITERASI ULTRASONOGRAFI DAN KESADARAN PEMERIKSAAN RADIOLOGI YANG AMAN - Ma’rifah, Alifatus Wahyu Nur; Kiren, Saddam Hamid Al; Azzahra, Azarine Aurelliahandy; Lagentu, Eby Patricia; Muttaqin, Iyadz; Mevia, Nova Eka Arta; Rafida, Putri Citra; Desitasari, Firnanda (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: In many regions, including Surabaya, ultrasonography (USG) remains underutilized for the early detection of non-obstetric conditions due to limited public understanding of its diagnostic value. This lack of awareness poses a challenge to the optimal delivery of healthcare services. Objective: This community service program aimed to increase public knowledge about the role of ultrasonography in healthcare through the ULTRASAFE (Ultrasound Literacy and Radiology Awareness for Safe Examinations) initiative. Method: The activity consisted of two sessions. The first involved a presentation and discussion with 35 participants from Bronggalan, Surabaya. The second included a mobile outreach session through the distribution of brochures and posters, accompanied by a question-and-answer segment. Evaluation was conducted using pre-tests and post-tests to assess knowledge improvement. Results: Following the discussion and interactive presentations, participants demonstrated a clear understanding of the benefits of ultrasonography imaging. The program significantly improved participants’ knowledge, as reflected in the increase of the mean score from 83.11% to 95.98%, with an N-gain value of 0.76. Conclusion: The ULTRASAFE activity effectively enhanced public literacy and attitudes toward ultrasonography as a diagnostic tool at Bronggalan, Surabaya.